Improved V.C.R. System by Using Sub-Cooling and Diffuser - Narwal, Amit; Kumar, Sarvesh; Verma, Rishabh; Kumar, Ravi (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2014)
This paper aims to improve coefficient of performance of system. To improve the coefficient of performance, it should be noted that compressor work should decrease and refrigerating effect should increase. Modifications in condenser are meant to increase degree of sub-cooling of refrigerant which increased refrigerating effect or more cooling water is required in condenser. The purpose of a compressor in vapour compression system is to elevate the pressure of the refrigerant, but refrigerant leaves the compressor with comparatively high velocity which may cause splashing of liquid refrigerant in the condenser tube, liquid hump and damage to condenser by erosion. It is needed to convert this kinetic energy to pressure energy by using diffuser. By using diffuser power consumption is less for same refrigerating effect so performance is improved.